2020
DOI: 10.1017/s0022377820000227
|View full text |Cite
|
Sign up to set email alerts
|

Improved performance of stellarator coil design optimization

Abstract: Following up on earlier work which demonstrated an improved numerical stellarator coil design optimization performance by the use of stochastic optimization (Lobsien et al., Nucl. Fusion, vol. 58 (10), 2018, 106013), it is demonstrated here that significant further improvements can be made – lower field errors and improved robustness – for a Wendelstein 7-X test case. This is done by increasing the sample size and applying fully three-dimensional perturbations, but most importantly, by changing the design sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…Numerically, the perturbations are independent of the coil discretization by considering additive perturbations modeled by Gaussian Processes (GPs). Similar approaches to model coil perturbations for stellarators have been presented in [21,34]. Compared to [34], instead of a squared exponential kernel with added periodicity, we take the period kernel as the basis for our perturbations.…”
Section: Coil Fabrication Uncertaintymentioning
confidence: 99%
See 2 more Smart Citations
“…Numerically, the perturbations are independent of the coil discretization by considering additive perturbations modeled by Gaussian Processes (GPs). Similar approaches to model coil perturbations for stellarators have been presented in [21,34]. Compared to [34], instead of a squared exponential kernel with added periodicity, we take the period kernel as the basis for our perturbations.…”
Section: Coil Fabrication Uncertaintymentioning
confidence: 99%
“…This allowed the reduction of engineering coil tolerances significantly [16]. Furthermore, recent work has shown that stochastic optimization is a promising method to improve the robustness of the generated magnetic field to fabrication and alignment errors in the associated coils [21,34]. However, all aforementioned approaches do not globally explore the coil design space.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3-D optimization effort is encouraged by recent Wendelstein 7-X results (Klinger et al 2019), which was optimized for neoclassical transport (Nührenberg & Zille 1986). There are new methods in coil-design, such as using permanent magnets (Helander et al 2020;Landreman & Zhu 2020;Zhu et al 2020) and designing coils with generous tolerances (Lobsien, Drevlak & Pedersen 2018;Lobsien et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…2020) and designing coils with generous tolerances (Lobsien, Drevlak & Pedersen 2018; Lobsien et al. 2020).…”
Section: Introductionmentioning
confidence: 99%